Rationale and design of leveraging the HIV platform for hypertension control in Africa: protocol of a cluster-randomised controlled trial in Uganda - Emmy Okello; Heiner Grosskurth; Moses Kamya; Gerald Mutungi; Starley B Shade; Mucunguzi Atukunda; Jane Kabami; Brian Twinamatsiko; Joan Nangendo; Edwin Charlebois (BMJ Open)
Introduction There is a high burden of hypertension (HTN) among HIV-infected people in Uganda. However, capacity to prevent, diagnose and treat HTN is suboptimal. This study seeks to leverage the existing HIV-related infrastructure in primary care health facilities (HFs) using the integrated HIV/HTN care model to improve health outcomes of patients with HIV and HTN.Methods and analysis Integrated HIV/HTN study a type-1 effectiveness/implementation cluster randomised trial, will evaluate the effectiveness of a multicomponent model intervention in 13 districts randomised to the intervention arm compared with 13 districts randomised to control. Two randomly selected HFs per district and their patients will be eligible to participate. The intervention will comprise training of primary healthcare (PHC) providers followed by regular supervision, integration of HTN care into HIV clinics, improvement of the health management information system, IT-based messaging to improve communication among frontline PHCs and district-level managers. HTN care guidelines, sphygmomanometers, patient registers and a buffer stock of essential drugs will be provided to HFs in both study arms. We will perform cross-sectional surveys at baseline, 12 and 24 months, on a random sample of patients attending HFs to measure effectiveness of the integrated care model between 2021 and 2024. We will perform in-depth interviews of providers, patients and healthcare managers to assess barriers and facilitators of integrated care. We will measure the cost of the intervention through microcosting and time-and-motion studies. The outcomes will be analysed taking the clustered structure of the data set into account.Ethics and dissemination Ethics approval has been obtained from the Research Ethics Committees at London School of Hygiene and Tropical Medicine, and Makerere University School of Medicine. All participants will provide informed consent prior to study inclusion. Strict confidentiality will be applied throughout. Findings will be disseminated to public through meetings, and publications.Trial registration number NCT04624061